CVD PREPARED Mn-DOPED ZnO NANOWIRES - T.L. Phan; R. Vincent; D. Cherns; N.X. Nghia (Universitas Gadjah Mada, 2007)
Mn-doped ZnO nanowires prepared by chemical vapor deposition (CVD) were obtained in the temperature range of 450–500°C. X-ray diffraction patterns, SEM and TEM images indicate that crystals with a hexagonal structure grow along the c axis. At low Mn-doped concentrations, photoluminescence (PL) and Raman scattering (RS) spectra are almost independent of the Mn doping. However, the increase in concentration of Mn above 1.6 at% weakens significantly the PL signal and the RS-lines intensity in the low wavenumber range of 300–480 cm-1, and concurrently increases the RS-lines intensity in the higher wavenumber range of 480-700 cm-1.. Magnetic measurements determined the Curie temperature of Mn-doped ZnO nanowire to be about 37 K.